The association of degree of polypharmacy before and after among hospitalised internal medicine patients and clinical outcomes: a retrospective, population-based cohort study - Martin I Sigurdsson; Adalsteinn Gudmundsson; Freyja Jónsdóttir; Anna B Blondal; Ian Bates; Jennifer Mary Stevenson (BMJ Open)
Objectives To determine the prevalence and incidence of polypharmacy/hyperpolypharmacy and which medications are most prescribed to patients with varying burden of polypharmacy.Design Retrospective, population-based cohort study.Setting Iceland.Participants Including patients (≥18 years) admitted to internal medicine services at Landspitali – The National University Hospital of Iceland, between 1 January 2010 with a follow-up of clinical outcomes through 17 March 2022.Main outcomes measures Participants were categorised into medication use categories of non-polypharmacy (<5), polypharmacy (5–10) and hyperpolypharmacy (>10) based on the number of medications filled in the year predischarge and postdischarge. The primary outcome was prevalence and incidence of new polypharmacy. Secondary outcomes were mortality, length of hospital stay and re-admission.Results Among 85 942 admissions (51% male), the median (IQR) age was 73 (60–83) years. The prevalence of preadmission non-polypharmacy was 15.1% (95% CI 14.9 to 15.3), polypharmacy was 22.9% (95% CI 22.6 to 23.2) and hyperpolypharmacy was 62.5% (95% CI 62.2 to 62.9). The incidence of new postdischarge polypharmacy was 33.4% (95% CI 32.9 to 33.9), and for hyperpolypharmacy was 28.9% (95% CI 28.3 to 29.5) for patients with preadmission polypharmacy. Patients with a higher level of medication use were more likely to use multidose drug dispensing and have a diagnosis of adverse drug reaction. Other comorbidities, including responsible subspeciality and estimates of comorbidity and frailty burden, were identical between groups of varying polypharmacy. There was no difference in length of stay, re-admission rate and mortality.Conclusions Preadmission polypharmacy/hyperpolypharmacy and postdischarge new polypharmacy/hyperpolypharmacy is common amongst patients admitted to internal medicine. A higher level of medication use category was not found to be associated with demographic, comorbidity and clinical outcomes. Medications that are frequently inappropriately prescribed were among the most prescribed medications in the group. An increased focus on optimising medication usage is needed after hospital admission.Trial registration number NCT05756400.